Abortion and Directive Genetic Counseling. Issue 2 (12th April 2023) - Kearney, Matthew
Abstract: This multi-method study uses statistical and comparative-historical investigations to find that abortion values shape genetic counseling practices across societies. Genetic counselors and genetically interested social scientists have long questioned, but never systematically demonstrated, whether this relationship exists. Genetic counseling data are drawn from cross-national surveys of genetic counselors ( n = 2, 906) from the mid-1990s, the key historical moment after this profession was globally established but before potentially confounding transnational professional effects. Data focus on Trisomy 21, severe open spina bifida, and Huntington's chorea. Abortion data are drawn from a new comparative-historical investigation of abortion attitudes in 36 countries based on law, frequency of policy debate, incidence rates, and public opinion polling. The key overall finding is that the more controversial abortion is within a society, the less directive genetic counselors are willing to be, whereas the less controversial abortion is, the more directive the counseling. Polynomial regressions, t -tests, likelihood ratios, and Wald tests provide statistical evidence for the relationship observed through qualitative clustering.